The cancer treatment revolution : - Nathan, David G. (John Wiley & Sons, 2007)
"The cancer treatment revolution" is both an examination of the history of cancer research and a celebration of the medical professionals, scientific researchers, and courageous patients who refuse to give up in the face of illness.